A Portable Magnetometer for Magnetic Measurements of Meter‐Sized Meteorites. (4th November 2020) - Clavé, Elise; Maurel, Clara; Lima, Eduardo A.; Shah, Jay; Mansbach, Elias N.; Uehara, Minoru; Weiss, Benjamin P.
Abstract: Meteorites contain records of past magnetic fields in the form of natural remanent magnetization (NRM). A key property of meteorite magnetization that provides information about its origin is its dependence on spatial scale. In particular, understanding how the mean remanent magnetization varies from the scale of meteorites to the global scale of their parent bodies would aid in the interpretation of spacecraft magnetometry data. However, the vast majority of meteorite samples whose remanent magnetization have been measured have sizes <10 cm due to the limited size range accommodated by laboratory magnetometers. To address this limitation, we developed a portable magnetometer array that enables remanence measurements of meter‐size meteorites in a non‐magnetically shielded environment. The instrument measures both NRM and induced magnetization using two orthogonal square Helmholtz coil pairs that compensate the vertical and horizontal components of the background magnetic field. An array of four magnetometers mounted on a movable aluminum rail measures the magnetic field at multiple locations around the sample. The instrument is transportable and can be adapted to different sample sizes. After distinguishing the induced component from the remanent component of a sample's total field, the remanence can be estimated from a multipole field inversion combined with nonlinear least squares method. We validated the instrument and data processing on a magnet of known magnetic moment and measured the NRM of a meter‐sized iron meteorite. Plain Language Summary: Meteorites are remnant fragments of planetary bodies. Their physical properties reflect the history of their environment and that of on their parent bodies. In particular, some meteorites preserve records of past magnetic fields experienced on their parent asteroids in the form of natural remanent magnetization. This remanence can be probed by spacecraft magnetometers to infer the intensity and direction of ancient magnetizing fields. However, it is unclear how to relate global scale measurements of planetary magnetization to that of meteorites measured in the laboratory. A major limitation is that the scaling of meteorite magnetization with size is largely unknown. Establishing such scaling requires measuring the remanent magnetizations of larger and larger meteorites. However, nearly all meteorites previously analyzed were typically smaller than ∼10 cm in diameter owing to the limited size and portability of the instruments. To facilitate the measurements of larger meteorites, we designed and built a portable instrument that enables measurements of the remanent and induced magnetizations of meter‐size meteorites at their storage location. We validated the instrument performance against a sample of known magnetic moment and then used it to measure a large iron meteorite. Key Points: Understanding planetary remanent magnetism benefits from measurements at spatial scales ranging from hand samples to global maps We designed a portable magnetometer array and data processing that allows on‐site magnetic measurements of up to meter‐size objects This system enables estimation of the net magnetic moment of some of the largest known meteorites on Earth